Differentiation of bovine from porcine gelatin capsules using gel electrophoresis method. (15th February 2019) - Yap, Beow Keat; Gam, Lay-Harn
Highlights: A new method to distinguish bovine from porcine gelatin capsule is proposed. Gel electrophoresis-based method is superior to the conventional PCR-based method. It is simple, rapid, accurate, economical and reliable. Abstract: Gelatin is commonly used in food supplements and in the form of soft or hard capsules. The source of gelatins is usually from porcine and bovine, and less commonly from vegetable and fish. Nevertheless, these different origins of gelatin have much similarity in term of structures, physicochemical properties and amino acid sequences. Due to these reasons, differentiation of the source of gelatins has been very difficult. In our present study, differentiation of sources of gelatin was made possible in a simplified yet economical method. Sample was prepared using ammonium sulfate precipitation and subjected to gel electrophoresis for protein separation. We have found a fraction of proteins which is able to differentiate porcine and bovine gelatins accurately, with distinctive protein bands in SDS-PAGE at 140 kDa and 110 kDa for bovine and porcine samples, respectively. This method was verified by 13 double-blinded gelatin samples, all the 13 samples were accurately identified.